The Socioeconomic Impact of Online Gambling on Economic Stability in Indonesia: A Policy-Oriented Analysis - Sudaryono Sudaryono; Poso Nugroho; Tommy Kuncara (Asosiasi Dosen Muda Indonesia, 2025)
The rapid rise of online gambling in Indonesia has created widespread concern due to its significant economic and social consequences. Despite being illegal, the accessibility and growth of digital platforms have made online gambling increasingly prevalent, with transaction values estimated to have reached IDR 327 trillion by 2023. This study aims to examine the socioeconomic impact of online gambling on household financial stability, labor productivity, and consumption behavior, as well as to assess the effectiveness of current regulatory responses. Using a qualitative descriptive approach, this research analyzes secondary data from official reports, media sources, and peer-reviewed literature. Thematic content analysis reveals five critical dimensions of impact: financial instability, rising household debt, reduced work productivity, diversion of household expenditure, and weak policy enforcement. The study also illustrates a sharp increase in online gambling activities over the past five years, indicating a growing threat to national economic resilience. This research contributes theoretically to the discourse on informal digital economies and behavior-driven financial risk. Practically, it calls for integrated policy responses involving financial literacy, regulatory reform, digital surveillance, and social protection mechanisms. A holistic, multi-sectoral approach is necessary to mitigate the economic harm caused by online gambling and safeguard vulnerable communities.